Heterogeneous photocatalytic Cr(VI) reduction with short and long nanotubular TiO2 coatings prepared by anodic oxidation - Vera, Maria Laura (2018)
Nanotubular TiO2 coatings prepared by anodic oxidation of titanium were evaluated for the first time in the photocatalytic Cr(VI) reduction in the presence of EDTA. Small nanotubes (SN) were prepared by using aqueous hydrofluoric acid as electrolyte, and long nanotubes (LN) were made by using an ethylene glycol solution containing ammonium fluoride and water. The samples were characterized by scanning electron microscopy, X-ray diffraction and UV–Vis diffuse reflectance spectroscopy. The photocatalytic reactions were performed using [Cr(VI)]0 = 0.8 mM, an EDTA/Cr(VI) molar ratio = 1.25 and pH 2. The photocatalytic activity increased with the applied voltage due to an increase of the average diameter, wall thickness and length of the nanotubes. The most active SN coating yielded 98% of Cr(VI) transformation after 300 min, while all LN samples achieved a complete transformation in the same time or less. The photocatalytic activity was in almost cases higher than that of a P25 supported sample.